2019
DOI: 10.1007/s12350-019-01650-x
|View full text |Cite
|
Sign up to set email alerts
|

How to detect and correct myocardial creep in myocardial perfusion imaging using Rubidium-82 PET?

Abstract: Reliability of myocardial blood flow (MBF) quantification in myocardial perfusion imaging (MPI) using PET can majorly be affected by the occurrence of myocardial creep when using pharmacologically induced stress. In this paper, we provide instructions on how to detect and correct for myocardial creep. For example, in each time frame of the PET images the myocardium contour and the observed activity have to be compared to check for misalignments. In addition, we provide an overview of the functionality of commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…This motion may cause the blood pool inside the LV to overlap with the inferior wall contour, which has a significant impact on MBF and MFR values in the corresponding RCA territory. Due to this, MFR values in the RCA territory are the most susceptible to variability resulting from subjective, manual motion correction [2,3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This motion may cause the blood pool inside the LV to overlap with the inferior wall contour, which has a significant impact on MBF and MFR values in the corresponding RCA territory. Due to this, MFR values in the RCA territory are the most susceptible to variability resulting from subjective, manual motion correction [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…For the correct calculation of MFR, it is necessary to align the heart images in the rest and stress studies in the appropriate axes. Moreover, as some authors emphasize, the quality of the study is influenced by artifacts resulting from the movement of the heart during the study (the so-called "cardiac creep" phenomenon-a change in the heart position, probably caused by faster and deeper breathing in response to dipyridamole) [2,3]. Therefore, it is also necessary to perform motion correction while processing the study.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 However, this influence can be limited by correcting the dynamic time-frames for possible motion and ''myocardial creep''. 11 Last, the test-retest reliability of MBF quantification is relatively large with a typical uncertainty of 21%. 12 This implies that there is a large 'grey area' in distinguishing reduced and normal MBF values and physicians should be aware of this during interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…2 Cardiorespiratory motion during acquisitions is another issue for MBF examinations, where the cardiorespiratory motion might introduce a general smear of the pathologic area. [7][8][9] Related to this issue is the wear-off of the pharmaceutical agents used for stress MBF examinations, resulting in changes of the respiratory depth and frequency [10][11][12] -a problem often referred to as ''myocardial creep''. This effect causes repositioning of the heart during scans, and consequently affects the time-activity curves used for the MBF evaluations.…”
mentioning
confidence: 99%
“…In the study, the authors reported most significant changes in the right coronary artery territory, with median changes in the MBF of 23% following MC, which is in concordance to previous studies. 11,15 Despite motion of up to 25 mm during the scans (myocardial creep), the authors reported that the impact of MC of the CTAC maps prior to image reconstruction resulted in relatively minor changes of the MBF (median change 5%), compared to the impact of the MC for the dynamic PET image-series alone (median change 12%). Although the finding is somewhat contradictory to the intuitive logic, similar findings have been reported for 82 Rb stress scans using regadenoson.…”
mentioning
confidence: 99%